PHASE : parental home-aided sex education - Sim, Jeremy Jian Ming (2019)
Despite multiple sources - including local organisations - stating that parents should be the primary educators of sex-related topics to their children, it is often the case that children get their first exposure to sex-related topics from school, friends and the internet instead. This is a cause for concern as children and teenagers are at a vulnerable age where they are still inexperienced and very much influenced by the deluge of information online that they are not able to discern right from wrong. Parents face multiple challenges when confronting sex education in Singapore. A “conservative” mindset is often donned when approaching the topic of sex, where parents do not talk much about it to their children and instead allow them to figure it out for themselves. There tends to be a general feeling of awkwardness and parents often do not feel the best equipped to impart such knowledge, often leaving it up to our national education system to handle it in the classrooms. Children may also feel that parents tend to be very judgemental and would shy away from discussing such topics openly with them. This project aims to rethink the way we confront the idea of sex and sex education within the current generation of children and teenagers in a way that engages the parents more, such that they play a bigger role in helping their children discern the various nuances and roles of sex in our Asian society, without judgement.